Development of CaO-rich blast furnace slag containing fluorine mica-based glass ceramic coatings - Ceylan, Iremnur; Gokdemir, Hatice; Cengiz, Tamer; Cicek, Bugra (ELSEVIER SCI LTD, 2021)
In the present study, Blast Furnace Slag (BFS) waste was evaluated as a sustainable, cost-effective CaO, SiO2, Al2O3 and MgO substitute for inorganic oxides for the production of frit, a raw material for glass ceramic production. Two different frits were prepared to compare a commercially available frit (F-STD) with frit produced using BFS waste (F-BFS). The samples were characterized by XRF, XRD, heating microscopy, dilatometry and TG-DTA to determine the chemical composition, phase formation and thermal properties. The frits were applied on steel using the electrostatic spray method and subsequently thermally treated at 830 degrees C for 4.5 min. The reference (GC-STD) and partially BFS-substituted glass ceramic (GC-BFS) coatings were examined by XRD, SEM-EDS and ICP-MS experiments. The main crystal phase for both samples was Ni-substituted fluorine mica (KLi-Ni2Si4O10F2). GC-BFS was slightly more amorphous (70%) than GC-STD (69.1%), which was correlated with the thermal properties of the BFS waste. Likewise, ICP-MS analysis after a boiling citric acid test (ISO 28706-1: 2008) revealed that the GC-BFS had relatively higher chemical resistance. The total release from the reference sample (GC-STD) was 23.556 mg/L, whereas the total release from the sustainably produced sample (GC-BFS) was 21.451 mg/L, which was consistent with the XRD results.
Keywords: Sustainable manufacturing; Waste disposal; Blast furnace slag; Frit; Glass ceramic coating; CRYSTALLIZATION; Materials Science